2007
DOI: 10.1111/j.1365-2222.2007.02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to montelukast is associated with bronchial hyperresponsiveness and total immunoglobulin E but not polymorphisms in the leukotriene C4 synthase and cysteinyl leukotriene receptor 1 genes in Korean children with exercise‐induced asthma (EIA)

Abstract: The LTC4S A(-444)C and CysLTR1 T(+927)C genotypes do not appear to be useful for predicting clinical responsiveness to montelukast, whereas bronchial hyperresponsiveness and total IgE appear to predict the degree of montelukast responsiveness in Korean asthmatic children with EIB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
1
25
1
Order By: Relevance
“…The other four published studies could not reproduce these findings (144,145,147,148). As these results were obtained in different populations and using different end points, this suggests that, although not sufficient to explain the variation in patient response to LTRAs, this polymorphism is a strong candidate and is potentially exerting its influence with other gene polymorphisms.…”
Section: Lt Pharmacogeneticscontrasting
confidence: 43%
See 1 more Smart Citation
“…The other four published studies could not reproduce these findings (144,145,147,148). As these results were obtained in different populations and using different end points, this suggests that, although not sufficient to explain the variation in patient response to LTRAs, this polymorphism is a strong candidate and is potentially exerting its influence with other gene polymorphisms.…”
Section: Lt Pharmacogeneticscontrasting
confidence: 43%
“…In a Korean population of 100 children with exercise-induced asthma, the synonymous coding CYSLTR1 polymorphism T>C (rs320995) did not affect the efficacy of montelukast to improve FEV 1 (148), but the minor alleles of both the promoter and coding SNPs [C>T (rs321029) and T>C (rs320995)] were associated with requirement for montelukast in another Korean population of 89 aspirin intolerant asthmatics (p < 0.02) (144). Carriers of the variants of two polymorphisms in the CYSLTR1 gene (rs91227 and rs912278) responded better to montelukast (145).…”
Section: Lt Pharmacogeneticsmentioning
confidence: 99%
“…Second, subjects were classified into PC 20 6 16 and PC 20 > 16 groups according to whether the value of the methacholine provocation test (PC 20 ) was above or below 16. Asthma was defined as PC 20 6 16 because PC 20 values below 16 represent BHR [12,13]. Peripheral blood was taken from all subjects for DNA isolation.…”
Section: Subjectsmentioning
confidence: 99%
“…Five of the ten published pharmacogenetic studies on the LTC4S -444 A>C polymorphism showed an improved response to LTRAs (FEV 1 ) from patients carrying the C allele [42,[44][45][46][47], although results were not always statistically significant [44,46,47]. The other five published studies could not reproduce these findings [43,[48][49][50][51]. More recently, a study of zileuton responses (FEV 1 change over time) in 577 asthma subjects failed to identify a pharmacogenetic effect of the LTC4S-444 polymorphism.…”
Section: Leukotriene C 4 Synthase (Ltc4s)mentioning
confidence: 99%